2007
DOI: 10.1108/01409170710832250
|View full text |Cite
|
Sign up to set email alerts
|

Determining the importance of key criteria in web usability

Abstract: Purpose -This research aims to investigate the relative importance of five key criteria in assessing web usability. These criteria are navigation, download speed, personalization, ease of use, and accessibility. It is believed that these factors play a significant role in assessing web usability. Design/methodology/approach -This study utilized a scenario-based, multi-criteria decisionmaking approach. The method (policy capturing) utilizes multiple scenarios to determine the relative importance of the criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 34 publications
3
53
1
4
Order By: Relevance
“…In addition to the recommended content elements on school websites, it is crucial to consider technical elements and design of the webpage, since functionality is critical for continued website usage (Pearson & Pearson, 2007). Hartshore et al (2008) provided suggestions for a website's technical and navigational elements, including features such as contrast, repetition, alignment, and proximity.…”
Section: School Website As Platform For Home-school Communication Andmentioning
confidence: 99%
“…In addition to the recommended content elements on school websites, it is crucial to consider technical elements and design of the webpage, since functionality is critical for continued website usage (Pearson & Pearson, 2007). Hartshore et al (2008) provided suggestions for a website's technical and navigational elements, including features such as contrast, repetition, alignment, and proximity.…”
Section: School Website As Platform For Home-school Communication Andmentioning
confidence: 99%
“…(26) the normalization process is applied using Eq. (12) and we achieve the following normalized performance matrix as shown in (27) http://journals.uob.edu.bh…”
Section: =008<10%mentioning
confidence: 99%
“…[ ] (27) Positive and negative ideal solution is evaluated using Eq. (14, 15, 16, and 17) to find the best and worst solution among alternatives.…”
Section: =008<10%mentioning
confidence: 99%
“…Stratification variables were selected based on the literature on web navigation and teacher professional development. Research has found that gender (Page, Robson, & Uncles, 2012;J. Pearson, A. Pearson, & Green, 2007), age (Laberge & Scialfa, 2005), subject matter knowledge and experience (Laberge & Scialfa, 2005), and computer self-efficacy (Page et al, 2012) influence the perception and navigation of websites; therefore, comparable aspects including gender, age, years of teaching experience, current teaching grade, comfort with technology, and frequency of Internet use for professional purposes, were selected as the key variables used for the group assignment.…”
Section: Data Sourcesmentioning
confidence: 99%